2020
DOI: 10.1074/jbc.ra119.011727
|View full text |Cite
|
Sign up to set email alerts
|

The retina and retinal pigment epithelium differ in nitrogen metabolism and are metabolically connected

Abstract: Defects in energy metabolism in either the retina or the immediately adjacent retinal pigment epithelium (RPE) underlie retinal degeneration, but the metabolic dependence between retina and RPE remains unclear. Nitrogen-containing metabolites such as amino acids are essential for energy metabolism. Here, we found that 15N-labeled ammonium is predominantly assimilated into glutamine in both the retina and RPE/choroid ex vivo. [15N]Ammonium tracing in vivo show that, like the brain, the retina can synthesize asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 60 publications
3
37
0
Order By: Relevance
“…Fig 6). We recently also reported that aspartate transamination is the primary pathway for the catabolism of aspartate and glutamate in mouse neural retinas 35 . As a major neurotransmitter, glutamate is the most abundant amino acid in the retina 36,37 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Fig 6). We recently also reported that aspartate transamination is the primary pathway for the catabolism of aspartate and glutamate in mouse neural retinas 35 . As a major neurotransmitter, glutamate is the most abundant amino acid in the retina 36,37 .…”
Section: Discussionmentioning
confidence: 90%
“…Retinal cells with the highest glutamate levels also have the highest aspartate levels 37 . We have previously reported that aspartate is utilized robustly to provide both carbons and nitrogen groups for glutamate synthesis 8,35,38 . Notably, aspartate transamination also generates oxaloacetate (OAA) which can be converted to malate by cytosolic malate dehydrogenase (MDH1) to carry electrons into mitochondria through the malate-aspartate shuttle (Fig 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearby MGCs and RPE provide much of the glutamine 62 , 157 , which when converted to glutamate via glutaminase (GLS) can either enter the catabolic TCA cycle or contribute to GSH generation (Fig. 6 ) 46 .…”
Section: Oxidative Stressmentioning
confidence: 99%
“…These tissue layers exhibit metabolic synergy in numerous ways. For example, the rods and cones of the photoreceptor layer perform aerobic glycolysis and provide the adjacent retinal pigment epithelium (RPE) with lactate [ 89 , 90 ], and the RPE synthesizes amino acids, such as glutamine and glutamate, to support photoreceptor metabolism and function [ 91 ]. Interestingly, although retinal pyruvate oxidation is minimal [ 89 , 90 ], the MPC appears to be essential for photoreceptor integrity and visual function [ 92 ].…”
Section: The Mpc In Post-development Health and Diseasementioning
confidence: 99%